(Nie)widzialne granice w relacjach polsko-niemieckich w świetle badań opinii publicznej = (In)visible borders in Polish-German relations in light of public opinion polls - Opiłowska, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The fall of the Iron Curtain, German reunification and Poland?s accession to the EU have opened a new chapter in the Polish-German relations. During the transformation period, Germany was perceived in Poland as an advocate for Polish interests in Europe. After Poland joined the EU in 2004, and then the Schengen area in 2007, the last "visible" barrier between Poland and Germany disappeared. However, it does not mean that also the invisible barriers of historical past, mutual prejudice and stereotypes have automatically disappeared. This article aims to analyze how Germans and Germany are perceived in Poland (and vice versa) and how, in light of the available opinion polls, both nations view mutual relations in Europe between the 1990s and the present day. It demonstrates the path to the German-Polish reconciliation and the existing barriers to building good neighborly relations.
Keywords: polsko-niemieckie relacje; granica; pojednanie; sąsiedztwo; wzajemne postrzeganie; German-Polish relations; borders; reconciliation; neighborhood; mutual perception